The Potential Role of Soluble Angiotensin Converting Enzyme 2 As A Left Ventricular Dysfunction Biomarker - Laksono, Sidhi; Setianto, Budhi; Prawara, Ananta Siddhi (Journal of Medicine, 2021)
Left ventricular (LV) dysfunction is a part of the common pathophysiologic mechanism for the development of heart failure (HF). LV dysfunction can be classified into left ventricular systolic dysfunction (LVSD) and left ventricular diastolic dysfunction (LVDD). Currently, B-type Natriuretic Peptide (BNP) and N-Terminal Pro-BNP (NT-proBNP) are the most common marker used to determine HF. Both of them are used as diagnostic and prognostic marker. Angiotensin Converting Enzyme 2 (ACE2) was found as an ACE homolog, located in the cell membrane of the heart. ACE2 has a cardioprotective role in turning AngII to Ang1-7. ACE2 can be cleaved by A Disintegrin and Metalloproteinase 17 (ADAM17)/TNF-a converting enzyme (TACE) so that it can be detected in the plasma as soluble ACE2. Soluble ACE2 possessed a potential role as LV dysfunction diagnostic or prognostic biomarker. J MEDICINE 2021; 22: 127-131